Relations of Knowledge with Perceptions of Eligible Men About Vasectomy in Angsau Primary Health Care, Tanah Laut, South Kalimantan - Natasha Bharat Sindunata Sindunata; Laili Wahyuni; Androniko Setiawan (Universitas Airlangga, 2021)
Background: Indonesia’s Maternal Mortality Rate (MMR) in 2015 was still high around 305 over 100.000 population. South Kalimantan MMR’s in 2018 increase to 108 over 100.000 population. If not handled properly the increasing of MMR, it will not achieve the SDG's by 2030. The high MMR is caused by the large number of pregnancies and deliveries in Indonesia. One of the ways to prevent it, is by reducing the number of pregnancies and one of the most effective way is through the Family Planning (FP) program. Vasectomy is a method of operative contraception in men. Public perception of vasectomy is a complicated operation, so vasectomy is not an option. Aim: Knowing the relations between knowledge and perceptions of eligible men on vasectomy Method: This research is an analytical survey with a cross sectional approach. The number of subjects used as many as 80 respondents who meet the feasibility of being included in this study. The chi-square test with a significance level of p<0.05 was used for statistical analysis. Knowledge is considered good if it has a total score of more than 76 percent, and it is considered poor if it is less than equal to 76 percent. Positive perception if the respondent's mean score is less than the T score, and to be negative perception if the respondent's mean score is more than the T score. Results: A total of 108 respondents were included in this study. There are 89 respondents or 82% who have good knowledge and 19 respondents or 18% who have bad knowledge about vasectomy. Negative perceptions were owned by 81 respondents or 75% while positive perceptions were only found in 27 respondents or 25%. Chi-square analysis showed that there was a significant relation between poor knowledge and negative perceptions with p<0.05. Conclusion: Poor knowledge of vasectomy is associated with negative perceptions. This study shows lack of public knowledge about vasectomy, causing a negative stigma about vasectomy.